Enhancement of Facilitation Training for Aphasia by Transcranial Direct Current Stimulation - Ihara, Aya S.; Miyazaki, Akiko; Izawa, Yukihiro; Takayama, Misaki; Hanayama, Kozo; Tanemura, Jun (Frontiers in Human Neuroscience, 2020)
We aimed to enhance the performance of naming and sentence production in chronic post-stroke aphasia by tablet-based language training combined with transcranial direct current stimulation (tDCS) conducted on non-consecutive days. We applied a deblocking method involved in stimulation–facilitation therapy to six participants with chronic aphasia who performed naming and sentence production tasks for impaired modalities, immediately after a spoken word–picture matching task for an intact modality. The participants took part in two conditional sessions: a tDCS condition in which they performed a spoken word–picture matching task while we delivered an anodal tDCS over the left inferior frontal cortex; and a sham condition in which sham stimulation was delivered. We hypothesized that, compared with the sham stimulation, the application of anodal tDCS over the left inferior frontal cortex during the performance of tasks requiring access to semantic representations would enhance the deblocking effect, thereby improving the performances for subsequent naming and sentence production. Our results showed greater improvements two weeks after training with tDCS than those after training with sham stimulation. The accuracy rate of naming was significantly higher in the tDCS condition than in the sham condition, regardless of whether the words were trained or not. In addition, we found a significant improvement in the production of related words and sentences for the untrained words in the tDCS condition, compared with that found pre-training, while in the sham condition we found no significant improvement compared with that found pre-training. These results support our hypothesis and suggest the effectiveness of the use of tDCS during language training on non-consecutive days.